Sensitivity of biological samples for Borrelia burgdorferi s.l. infection status assessment in avian hosts - Norte, A.C. (2020)
Avian hosts can act as reservoirs for Borrelia burgdorferi sensu lato (s.l.), a bacterial complex that includes the etiologic agents of Lyme borreliosis. It is relevant to evaluate the infection status of the bird species to elucidate their importance as reservoir hosts, because not all contribute equally to the maintenance of Borrelia. There is a lack of a reliable non-invasive technique that allows us to assess the infection status of B. burgdorferi s.l. in wildlife. Thus, the main goal of this study was to evaluate the usefulness of biological samples such as blood and skin biopsies from two avian model species, Turdus merula and Erithacus rubecula, to diagnose B. burgdorferi s.l. infection and give information on their infectivity to ticks. Blood and skin tissues were collected from 16 Erithacus rubecula and 10 Turdus merula captured in Borrelia enzootic areas. These birds were taken into captivity and subjected to xenodiagnoses. DNA was extracted from blood and skin samples and from the fed xenodiagnostic larvae, and analysed for B. burgdorferi s.l. infection by real-time PCR directed to the flaB gene. Sensitivity of these approaches to evaluate host’s infection status will be compared and will help to elucidate B. burgdorferi s.l tropism in the birds’ organism.